2018
DOI: 10.1111/are.13846
|View full text |Cite
|
Sign up to set email alerts
|

Effects of combined dietary administration ofRhodotorulasp. H26 andBacillussp. BC26 on growth, immunity and intestinal microbiota in juvenile sea cucumber,Apostichopus japonicus

Abstract: A 8‐week feeding trial was conducted to evaluate the effects of combined oral administration of the yeast Rhodotorula sp. H26 and bacterium Bacillus sp. BC26 on growth, digestive enzyme activity, body composition, immunity, and intestinal microbiota in the juvenile sea cucumber, Apostichopus japonicus. Sea cucumbers were divided into four groups and received one of the following diets: BD) basal diet; H) H26; B) BC26; HB) H26 + BC26. After feeding for 4 and/or 8 weeks, sea cucumbers fed the HB diet showed a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
(80 reference statements)
0
2
0
Order By: Relevance
“…Besides the terrestrial plants, animals and their products, S. echinoides is also present in the aquatic environment and found to be associated with various aquatic organisms. It was previously identified in the intestinal microbiota of cultured grass carp (Ctenopharyngodon idellus) in China (Zhou et al, 2013;Yuan et al 2015), among the surface-associated bacteria isolated from the sea cucumber Stichopus badionotus in Malaysia (Alipiah et al, 2016), in the microbiota of abalone (Haliotis discus hannai) in South Korea (Lee et al, 2016), among the intestinal microbiota of juvenile sea cucumber, Apostichopus japonicus (Ma et al, 2018) and among the surface-associated bacteria isolated from the sea urchin (Tripneustes gratilla) in South Africa (Brink et al, 2019). Besides, S. paucimobilis was also identified in the water released from a rainbow trout farm in Mersin region of Turkey (Özer et al, 2008) and a resistant strain of this species against various heavy metals and antibiotics was identified from the water column of Kızılırmak river (Özer et al, 2013;İçgen and Yılmaz, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Besides the terrestrial plants, animals and their products, S. echinoides is also present in the aquatic environment and found to be associated with various aquatic organisms. It was previously identified in the intestinal microbiota of cultured grass carp (Ctenopharyngodon idellus) in China (Zhou et al, 2013;Yuan et al 2015), among the surface-associated bacteria isolated from the sea cucumber Stichopus badionotus in Malaysia (Alipiah et al, 2016), in the microbiota of abalone (Haliotis discus hannai) in South Korea (Lee et al, 2016), among the intestinal microbiota of juvenile sea cucumber, Apostichopus japonicus (Ma et al, 2018) and among the surface-associated bacteria isolated from the sea urchin (Tripneustes gratilla) in South Africa (Brink et al, 2019). Besides, S. paucimobilis was also identified in the water released from a rainbow trout farm in Mersin region of Turkey (Özer et al, 2008) and a resistant strain of this species against various heavy metals and antibiotics was identified from the water column of Kızılırmak river (Özer et al, 2013;İçgen and Yılmaz, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…H26 and Bacillus sp. BC26 improved digestive enzyme activity (e.g., trypsin and amylase) and innate immune responses (phagocytic activity and lysozyme activity) in the juvenile sea cucumber Apostichopus japonicas [226].…”
Section: Combined Application Of Yeasts or Actinobacteria Along With ...mentioning
confidence: 99%
“…It has been reported that growth performance of sea cucumber can be much improved by dietary supplement of fermented soybean (FSB) (Seo et al, 2011b), solid-state fermented diet (Wang, Guo, et al, 2017) and hydrolysed soybean meal (Song et al, 2016). Moreover, several studies demonstrated that dietary probiotics had positive effects on the growth and immunity of sea cucumber (Chi et al, 2014;Ma et al, 2018;Yang et al, 2015). In the present study, serial feeding trials were conducted to determine the proper dietary supplement for Apostichopus japonicus (Selenka, 1867).…”
Section: Introductionmentioning
confidence: 99%